2020
DOI: 10.1007/s00423-020-01917-9
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein stent placement after hepatobiliary and pancreatic surgery

Abstract: Purpose To evaluate the long-term outcomes of percutaneous transhepatic stent placement for portal vein (PV) stenosis after liver transplantation (LT) and hepato-pancreato-biliary (HPB) surgery. Methods Retrospective study of 455 patients who underwent LT and 522 patients who underwent resection of the pancreatic head between June 2011 and February 2016. Technical success, clinical success, patency, and complications were evaluated for both groups. Results A total of 23 patients were confirmed to have postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, placement of a PV stent is not generally applied, most likely owing to a lack of sufficient evidence demonstrating its benefits to survival and because of its technical difficulties. A few investigators have reported on the usefulness of PV stent placement; however, these studies had a sample size of < 40 patients and used a single-arm methodology [ 8 15 16 17 18 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, placement of a PV stent is not generally applied, most likely owing to a lack of sufficient evidence demonstrating its benefits to survival and because of its technical difficulties. A few investigators have reported on the usefulness of PV stent placement; however, these studies had a sample size of < 40 patients and used a single-arm methodology [ 8 15 16 17 18 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent literature review by Khan et al suggests that portal vein stent placement following hepatobiliary and pancreatic surgery is a safe and effective treatment in patients with portal vein stenosis, with clinical success rates of 72%-100%, long-term patency of 57%-100%, and procedure-related complication rates of 0%-33.3% [12] . While this literature review included a heterogeneous population of post-surgical and liver transplant patients, we believe the technical success rates and complication rates are relatively generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of long-term anticoagulation following splanchnic vein stent dilation is not well understood. Studies have varied in their usage of anticoagulation with bleeding risk and the risk of stent thrombus formation factoring into this decision [12] . Interestingly, our patient developed partial occlusion of the SMV stent 1 week following the procedure at which time anticoagulation was resumed and the patient's symptoms quickly improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the therapeutic consequence of detecting an asymptomatic SMV-PV stenosis/occlusion is under debate. Due to increased risk of complications, the indication for percutaneous PV stent placement after pancreatectomy with venous resection and reconstruction is recommended to be limited to patients with clinical symptoms [42,43] . Most patients are asymptomatic, whereas others present with the typical clinical signs of portal hypertension, including gastrointestinal hemorrhage, ascites and splenomegaly [42] .…”
Section: Discussionmentioning
confidence: 99%